Pengelolaan Sampah Organik Rumah Tangga Berbasis Kompos Takakura di Kelurahan Kertosari Tahun 2025: Pengabdian - Rizkiana, Claradea; Novi Dian Arfiani; Auxilya Cahaya Putri Naswa; Tantra Dipta Prawira; Nastiti Ivory Putri Anggriyanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Household organic waste management remains a challenge at the community level due to low awareness, skills, and available facilities. This community service program aims to improve the knowledge and skills of Kertosari Village residents in managing organic waste using the Takakura Compost method. The activity was carried out in January 2025 with activities such as education, direct practice, monitoring, and evaluation involving 34 participants. The pre-test results showed that 44.1% of participants received a perfect score, an increase of 64.7% in the post-test after the education and direct practice. In addition, 29.41% of participants began to apply the Takakura method at home collectively. The resulting compost had an average weight of 296.67 grams from 1000 grams of starting material and met the maturity indicators according to the SNI for household compost. These findings indicate that a practice-based educational approach can encourage changes in community behavior in independent waste management.